Communication relations on Twitter during the migrant “crisis” in Slovenia - Smrdelj, Rok (Dve domovini, 2024)
The article explores communication relations on Twitter during the 2015–2016 migrant “crisis” in Slovenia. By integrating social network analysis with critical discourse studies, the author finds that the “left-wing” political network had the most members. In contrast, the “right-wing” political network was notably more influential and active. The political elite, mass media, journalists, and public figures are among the most influential users. A vast majority of posts feature discriminatory discourse focused on security understandings of migration. The research is important because it provides one of the few and relatively comprehensive insights into the online digital discussion on migration in Slovenia.
Keywords: begunci; begunska kriza; diskurzivna analiza; družbena omrežja; množični mediji; Slovenija; Twitter